2020
DOI: 10.1063/1.5145253
|View full text |Cite
|
Sign up to set email alerts
|

Striped superlattice pattern in dielectric barrier discharge

Abstract: We report on the striped superlattice pattern in dielectric barrier discharge for the first time. The spatiotemporal structure of the striped superlattice pattern is investigated by a high-speed framing camera. The result shows that the striped superlattice pattern consists of three different transient sub-lattices which are striped-dots, stripes, and small-dots surrounding a striped-dot, respectively. Images of a single frame indicate that the stripes which look like they are diffused are actually made up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…To obtain the distinct structure of the pattern, integrated photographs over multi-cycles are usually utilized first. Equally, the instantaneous photographs obtained in one voltage cycle are indispensable for getting to know the essential attributes of the patterns [22,26]. Hence, the photographs in one voltage cycle whose exposure time consistent with the results obtained with ICCD.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…To obtain the distinct structure of the pattern, integrated photographs over multi-cycles are usually utilized first. Equally, the instantaneous photographs obtained in one voltage cycle are indispensable for getting to know the essential attributes of the patterns [22,26]. Hence, the photographs in one voltage cycle whose exposure time consistent with the results obtained with ICCD.…”
Section: Resultssupporting
confidence: 70%
“…In recent years, the DBD system, known for its incredible accessibility and utility for experimental devices, has been verified as an amazing and preferred system for the investigation of pattern dynamics, because it exhibits an exceptionally great variety and abundance of self-organized patterns [16][17][18][19][20][21][22][23]. Due to the luminous intensity, there not only exist visible discharge filaments to the naked eye or an ordinary camera, which is called normal discharge, but also discharge filaments exist that are invisible to the naked eye or an ordinary camera, which called dark discharge in the DBD system.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Feng et al discovered a stripe superlattice pattern consisting of three different sublattices in the DBD system. 13 Here, we report a (bright spots)-(dark spots)-halo stripe pattern (BDHSP) in the DBD system. The direction of the stripe choose to form is related to the directional selective surface discharge of the pattern, which appears before the evolution to BDHSP.…”
Section: Introductionmentioning
confidence: 84%
“…[3][4][5][6][7] Various luminescent patterns have been obtained, such as square patterns, hexagonal patterns, honeycomb patterns, and stripe patterns. [8][9][10][11][12][13] Among them, the stripe pattern has been extensively investigated owing to its typical symmetry. In 1995, Breazeal et al found stripe patterns in the He gas discharge system.…”
Section: Introductionmentioning
confidence: 99%